Survival of radioiodine treated hyperthyroid cats that are euthyroid and hypothyroid after treatment, and effect of levothyroxine supplementation on survival time of cats with iatrogenic hypothyroidism - Sarah E. Cox; Jennifer Wakeling; Teresa Hall; Tim L. Williams (Journal of Veterinary Internal Medicine)
Abstract Background Hyperthyroid cats that are azotemic and hypothyroid after surgical or medical treatment have poor outcomes, and supplementation with levothyroxine (LT4) improves survival. However, the effect of LT4 supplementation on survival of nonazotemic, hypothyroid radioiodine (RI)‐treated hyperthyroid cats is unknown. Hypothesis Radioiodine treated hyperthyroid cats with iatrogenic hypothyroidism or azotemia have shorter survival times than euthyroid, nonazotemic cats and supplementation of LT4 improves survival times of hypothyroid cats. Animals One hundred seventeen RI treated hyperthyroid cats. Methods Prospective cohort study. Radioiodine treated cats were screened for azotemia and iatrogenic hypothyroidism using TSH stimulation test; LT4 supplementation was offered to all hypothyroid cats with decision to treat based on owner preference. The log rank test was used to compare survival times between groups, and the Mann‐Whitney U test was used to compare age and renal variables. Data are presented as median [range]. Results Euthyroid azotemic cats (934 [759‐2035] days) and nonsupplemented hypothyroid cats (azotemic and nonazotemic combined, 1232 [238‐2363] days) had shorter survival times than euthyroid nonazotemic cats (1616 [663‐3369] days, P = .003 and P = .002, respectively). Levothyroxine supplemented hypothyroid nonazotemic cats had longer survival times than nonsupplemented hypothyroid nonazotemic cats (1037 [300‐2401] days vs 768 [34‐1014] days; P = .027). Levothyroxine supplementation was not associated with prolonged survival times in hypothyroid azotemic cats vs nonsupplemented hypothyroid azotemic cats (771 [718‐1558] days vs 152 [82‐1852] days, respectively, P = .991). Conclusions and Clinical Importance Levothyroxine supplementation in nonazotemic cats with iatrogenic hypothyroidism (diagnosed based on TSH stimulation test results) improved survival times, although randomized controlled trials are needed.